Possibilities of introducing an intelligent control system in the flotation plant Veliki Krivelj - Jovanović Ivana; Magdalinović Srđana; Mikić Miomir; Miljanović Igor (Mining and Metallurgy Engineering Bor, 2017)
In this paper, an analysis of the possibility of implementing the fuzzy logic and artificial neural network controller in the intelligent control system in the flotation plant Veliki Krivelj was performed. Functional positioning of controllers was considered through two approaches. According to one approach, the control of flotation process would be carried out by only one controller, while in the second case two controllers would exist - one for a rough flotation and scavenging and the other for cleaning.